The Cambridge handbook of disaster law and policy : risk, recovery, and redevelopment / edited by John Travis Marshall, Georgia State University College of Law, Ryan Rowberry, Georgia State University College of Law, Susan S. Kuo, University of South Carolina School of Law. - Marshall, John Travis; Kuo, Susan S., 1969-; Rowberry, Ryan (Cambridge University Press, 2022)
This century's major disasters from Hurricane Katrina and the Fukushima nuclear meltdown to devastating Nepalese earthquakes and the recent crippling volcanic eruptions and tsunamis in Tonga have repeatedly taught that government institutions are ill-prepared for major disaster events, leaving the most vulnerable among us unprotected. These tragedies represent just the beginning of a new era of disaster - an era of floods, heatwaves, droughts, and pandemics fueled by climate change. Laws and government institutions have struggled to adapt to the scope of the challenge; old models of risk no longer apply. This Handbook provides timely guidance, taking stock of the field of disaster law and policy as it has developed since Hurricane Katrina. Experts from a wide range of academic and practical backgrounds address the root causes of disaster vulnerability and offer solutions to build more resilient communities to ensure that no one is left behind.